Plasma Treated Water Solutions in Cancer Treatments: The Contrasting Role of RNS - Eloisa Sardella; Valeria Veronico; Roberto Gristina; Loris Grossi; Savino Cosmai; Marinella Striccoli; Maura Buttiglione; Francesco Fracassi; Pietro Favia (MDPI AG, 2021)
Plasma Treated Water Solutions (PTWS) recently emerged as a novel tool for the generation of Reactive Oxygen and Nitrogen Species (ROS and RNS) in liquids. The presence of ROS with a strong oxidative power, like hydrogen peroxide (H2O2), has been proposed as the main effector for the cancer-killing properties of PTWS. A protective role has been postulated for RNS, with nitric oxide (NO) being involved in the activation of antioxidant responses and cell survival. However, recent evidences proved that NO-derivatives in proper mixtures with ROS in PTWS could enhance rather than reduce the selectivity of PTWS-induced cancer cell death through the inhibition of specific antioxidant cancer defenses. In this paper we discuss the formation of RNS in different liquids with a Dielectric Barrier Discharge (DBD), to show that NO is absent in PTWS of complex composition like plasma treated (PT)-cell culture media used for in vitro experiments, as well as its supposed protective role. Nitrite anions (NO2-) instead, present in our PTWS, were found to improve the selective death of Saos2 cancer cells compared to EA.hy926 cells by decreasing the cytotoxic threshold of H2O2 to non-toxic values for the endothelial cell line.